A Competência normativa das agências reguladoras e seus limites principiológicos no direito brasileiro - Jales, Andréa Maria Pedrosa Silva (2013)
The transition of the liberal state to welfare state, globalization and the crisis of funding from the government spending on the multiple roles demanded an overhaul of the means of intervention in the economic domain and structure organizational of the Public Administration by enhancing the performance of regulatory functions. Therefore appear in Brazilian law independent regulatory agencies with legal administrative particular that gives autonomy increased, with fixed terms and stability of its leaders, police and competencies, normative and administrative judges. In this scenario, given the autonomy granted by the laws of the creation of regulatory agencies, the legislative competence becomes the most contentious issue, as not infrequently is innovation in the legal system. The main foundations of innovative extension producible by regulatory agencies, which diverges doctrine, are the constitutional attribution of own competence of the Public Administration and the discretionary power. Thus, it is necessary to delimit the constitutional and legal foundations of special legislative powers of these autarchies in our legal system, seeking ways to limit and control the production rules of those entities, for the purpose of position them before the powers constitutionally constituted. We note that with the constitutionalisation of administrative law regulatory agencies found limits to its performance in the normative constitutional principles, especially through the principles of efficiency, morality and proportionality, which has enabled a more effective control of their normative acts